2016
DOI: 10.1017/dmp.2015.156
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Community Participation in Earthquake Preparedness: A Community-Based Participatory Intervention Study of Tehran

Abstract: A participatory intervention effectively improved disaster preparedness at a community level. To ensure sustainability, the participatory approach should be integrated into public health disaster planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Age was mentioned in 7 articles (in one not as a significant factor [13]; in the others, it had direct [4,6,16,22] and/or indirect [10,19] effect on preparedness. This work indicated that younger people were inclined to be more aware and prepared [21]. Job position [4,11,16,19], income level and socioeconomic status [7,10,11,20], education [4,7,10,13,16,18,19,21] were identified as having both direct and indirect positive impacts on preparedness knowledge and behavior.…”
Section: Demographic Determinantsmentioning
confidence: 90%
See 4 more Smart Citations
“…Age was mentioned in 7 articles (in one not as a significant factor [13]; in the others, it had direct [4,6,16,22] and/or indirect [10,19] effect on preparedness. This work indicated that younger people were inclined to be more aware and prepared [21]. Job position [4,11,16,19], income level and socioeconomic status [7,10,11,20], education [4,7,10,13,16,18,19,21] were identified as having both direct and indirect positive impacts on preparedness knowledge and behavior.…”
Section: Demographic Determinantsmentioning
confidence: 90%
“…They have tried to identify both the barriers to earthquake preparedness and its facilitators. Most studies identified insufficient disaster preparedness of communities and households all over the country [4,7,10,11,13,15,[20][21][22].…”
Section: Earthquake Preparednessmentioning
confidence: 99%
See 3 more Smart Citations